Knit your own cat : easy-to-follow patterns for 16 frisky felines - Muir, Sally (Black Dog & Leventhal, 2011)
"This irresistible book is full of simple patterns to create your very own knitted cat. Choose from the pretty Persian, the sleek Siamese, the traditional Tabby, or over a dozen other breeds!" -- back cover.